EFFECT OF CURRENT RATIO (CR), RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER), EARNING PER SHARE (EPS) ON STOCK PRICES OF BUILDING CONSTRUCTION SUBSECTOR COMPANIES (J211 IDX-IC) LISTED ON THE IDX IN 2016-2021 - Evi Yustikasari; Ari Nurul Fatimah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
Investment activities in the company are supporting factors that can affect the sustainability of the company in the future. The nominal size of the stock price will be a consideration for investors in making investments. This study aims to analyze whether or not there is an influence of fundamental factors including ROA (return on Assets), ROE (return on equity), DER (debt equity ratio), EPS (earnings per share), and CR (current ratio) on stock prices in building construction subsector companies listed on the Indonesia Stock Exchange in 2016-2021. This research is included in the type of quantitative research using secondary data. The sample data collection technique uses the purposive sampling method where a sample of 24 companies from a population of 55 companies was obtained. The results showed that between 2016 and 2021, the share price of building sub-construction companies listed on the IDX was largely and partly influenced by the Return on Assets (ROA). Further, the share price of IDX-listed building sub-construction companies was significantly and partly influenced by the current ratio (CR). The share prices of building companies engaged in sub-construction were significantly and partially influenced by the debt equity ratio (DER). In addition, EPS will have a positive and significant impact on the share price of building sub-construction companies listed on the IDX.